Video-Based Pairwise Comparison: Enabling the Development of Automated Rating of Motor Dysfunction in Multiple Sclerosis - , Jessica Burggraaff, Jonas Dorn, Marcus D'Souza; Morrison, Cecily, Christian P. Kamm, Peter Kontschieder, Prejaas Tewarie, Saskia Steinheimer; Sellen, Abigail, Frank Dahlke, Ludwig Kappos, Bernard Uitdehaag (Archives of Physical Medicine and Rehabilitation, 2020)
To examine the feasibility, reliability, granularity, and convergent validity of a video-based pairwise comparison technique that uses algorithmic support to enable automated rating of motor dysfunction in patients with multiple sclerosis (MS).